2006
DOI: 10.1016/j.neuroimage.2006.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Aging: Compensation or maturation?

Abstract: Neuroimaging studies of healthy aging often reveal differences in neural activation patterns between young and elderly groups for episodic memory tasks, even though there are no differences in behavioral performance. One explanation typically offered is that the elderly compensate for their memory deficiencies through the recruitment of additional prefrontal regions. The present study of healthy aging compared magnetoencephalographic (MEG) time-courses localized to specific cortical regions in two groups of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 74 publications
(89 reference statements)
4
39
0
Order By: Relevance
“…In addition, postmortem evidence suggests that myelination of the hippocampus continues into the '5th and 6th decades of life' [53] . In fact, both Aine et al [42] and Raz et al [54] have reported an inverted U-shaped function for white matter volume in frontal cortex in which young and older adults have reduced volumes relative to middle-aged adults. It is possible that older adults utilize a different strategy than the young adults in part as a result of different maturational stages.…”
Section: Segmentation Measurementsmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, postmortem evidence suggests that myelination of the hippocampus continues into the '5th and 6th decades of life' [53] . In fact, both Aine et al [42] and Raz et al [54] have reported an inverted U-shaped function for white matter volume in frontal cortex in which young and older adults have reduced volumes relative to middle-aged adults. It is possible that older adults utilize a different strategy than the young adults in part as a result of different maturational stages.…”
Section: Segmentation Measurementsmentioning
confidence: 97%
“…As Aine et al [42] suggest, methods used to examine age-related changes have limitations including use of the subtraction method, differences in resting state physiology, and differences in neurovascular coupling. Given this heterogeneity across studies, we further operationalize our proposed definition of compensatory mechanism recruitment by proposing a set of criteria to be considered when assessing whether a study's results are reflective of compensation.…”
Section: Additional Brain Regions And/or (2) Discrepant Brain Activamentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, vascular factors cannot fully explain the relationship between MTR and CVLT in the young. However, there are a number of maturational brain changes that continue into late adolescence (for a review see Paus, 2005), including proliferation of myelin into the peripheral cortical neuropil (Aine et al, 2006;Sowell et al, 2004;Yakovlev & Lecours, 1967), the formation and usage-dependent selective elimination of synapses (Hensch, 2004;Huttenlocher & Dabholkar, 1997), and metabolic changes (Chugani, Phelps, & Mazziotta, 1987), which could contribute to a reversed relationship between MTR and cognition in the young adults. Indeed, we observed that there was an age-related increase in MTRs of both regions within the group of the young adults (Fig.…”
Section: Reversed Correlations In the Youngmentioning
confidence: 99%